Development of E-Learning Learning Models in English Subjects - Raudatul Husna; Sukardi Sukardi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aims to develop and test an E-learning model for effective English teaching for class XI students in the Computer Network Engineering program at SMKN 3 Batam. This model aims to improve the quality of English language learning in the digital era. It follows a research and development (R&D) process that includes four stages: define, design, develop, and disseminate. Based on the evaluation results, this E-learning learning model has succeeded in increasing interactivity between students and teachers, increasing access to learning materials, and raising students' enthusiasm for learning English. It helps the independent development of English language skills through interactive activities, exercises, and online exams. Based on research findings, the effectiveness of the E-learning model is in the medium category, with a Gain Score test score of 0.54 indicating its success in improving student learning outcomes. Based on the findings of this research, it can be concluded that this e-learning model is valid, practical, and effective, offers an alternative English language learning that is innovative, effective, and relevant in the digital era, and can serve as a model for other schools interested in implementing language learning. Technology-based UK.